Betriebe und Frühverrentung: Angebote, die man nicht ablehnt - Lutz Bellmann; Florian Janik (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2010)
– In many countries early retirement has become a personnel strategy. The establishments are interested in hiring younger employees and try to avoid 'deferred payments' which arise if older employees are paid above their productivity. Firms enter into contracts with their employees that include clauses about early retirement. In response to demand or technological shocks, workers receive retirement offers from their employers which cannot be rejected by rational actors. Using the IAB Establishment Panel 2003-2006, the relation between indicators of demand and technological shocks and the incidence and quantity of early retirements is analyzed. Thus, our findings suggest that firms' personnel policies affect the employees' decisions about early retirement.
Keywords: 330; Frührentner; Personalpolitik; ältere Arbeitnehmer; Lohnhöhe; IAB-Betriebspanel; vorgezogene Altersgrenze; Vorruhestand; Berufsausstieg